Neuroesquistossomose experimental em camundongos: estudo clínico, anátomo-patológico e da ressonância magnética do encéfalo - Thiago Andre Alves Fidelis (2018)
In the year 2000, an estimated 8 million people were infected with Schistosoma mansoni and 30 million were at risk of infection in Brazil. The Global Burden of Disease Study 2010 indicated that schistosomiasis is the one hundredth cause of death in Brazil, and is responsible for 3.6% of the estimated total of deaths in the world. The central nervous system can also be affected by S. mansoni infection. Previous authors have observed helminth eggs in the leptomeninges, cerebral cortex, basal ganglia, choroid plexus, cerebellum and spinal cord, the latter of these with the highest frequency. In the present study, experimental infection of S. mansoni cercariae in mice aims to demonstrate the presence of granulomas formed in the brain and correlate the clinical, histologic, and magnetic resonance findings. We infected 25 male mice (Mus musculus-Swiss Webster), weighing between 18 and 20 grams, with 50 LE strain larvae subcutaneously, and maintained 25 as controls, without infection. We followed them for 160 days post-infection. Euthanasia was carried out on days 88, 97 and 146. After confirmation of death, brain samples were fixed in formalin. Parasites were recovered using the technique developed by Pellegrino and Siqueira (1956). Images were obtained in the axial, coronal and sagittal planes by magnetic resonance. Following imaging studies, we performed histological studies in order to examine S. mansoni eggs, granulomas and inflammatory lesions. The characteristic neuromotor behaviors observed was head and chest tilt, paresis, loss of balance reflex, altered muscle tone, ataxia and rotational motion (spinning). Histological findings included the presence of S. mansoni eggs disseminated in both hemispheres, in the cerebral, cerebellar and brainstem regions. Magnetic resonance imaging showed in T1 weighting hyperdense nuclei surrounded by a hypodense line in the different planes. Samples suggest eggs reached the brain through the arterial system. The granulomatous reaction was more frequent in the leptomeninge and in areas of ventricular fissures. Edema and leptomeningeal thickening were found. Eggs presented miracidia. Additionally, histological examination demonstrated macrophages, eosinophils, lymphocytes, fibroblasts and collagen in the samples. In conclusion, the experimental model of brain schistosomiasis mansoni was developed by injecting cercariae into the subcutaneous tissue. There was a correspondence between the encephalic lesions and the magnetic resonance findings.